2018
DOI: 10.1111/imcb.12037
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to chorioamnionitis alters the monocyte transcriptional response to the neonatal pathogen Staphylococcus epidermidis

Abstract: Preterm infants are uniquely susceptible to late-onset sepsis that is frequently caused by the skin commensal Staphylococcus epidermidis. Innate immune responses, particularly from monocytes, are a key protective mechanism. Impaired cytokine production by preterm infant monocytes is well described, but few studies have comprehensively assessed the corresponding monocyte transcriptional response. Innate immune responses in preterm infants may be modulated by inflammation such as prenatal exposure to histologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
35
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 52 publications
(97 reference statements)
8
35
2
Order By: Relevance
“…While this approach revealed that chorioamnionitis exposure altered gene expression in both innate and adaptive immune pathways, the approach made it impossible to determine which cells were responsible for these differences. A more recent study performed RNA‐seq on purified cord blood monocytes from very preterm neonates (<32 weeks) with and without chorioamnionitis exposure both before and after stimulation with the most common etiology of neonatal late onset sepsis, Staphylococcus epidermidis . This study found that chorioamnionitis exposure in preterm infants is associated with a hyporesponsive transcriptional profile, which may alter a preterm infants’ risk of sepsis.…”
Section: Discussionmentioning
confidence: 91%
“…While this approach revealed that chorioamnionitis exposure altered gene expression in both innate and adaptive immune pathways, the approach made it impossible to determine which cells were responsible for these differences. A more recent study performed RNA‐seq on purified cord blood monocytes from very preterm neonates (<32 weeks) with and without chorioamnionitis exposure both before and after stimulation with the most common etiology of neonatal late onset sepsis, Staphylococcus epidermidis . This study found that chorioamnionitis exposure in preterm infants is associated with a hyporesponsive transcriptional profile, which may alter a preterm infants’ risk of sepsis.…”
Section: Discussionmentioning
confidence: 91%
“…The Original Article by Emma de Jong et al ., “Exposure to chorioamnionitis alters the monocyte transcriptional response to the neonatal pathogen Staphylococcus epidermidis ”, was published in September 2018, is the winner of the Thermo Fisher Scientific Publication Award for 2018 . Dr de Jong and colleagues investigated the impact of chorioamnionitis, an infection of the placenta or amniotic fluid, on monocyte responses using whole transcriptome sequencing.…”
mentioning
confidence: 99%
“…The recent paper by de Jong et al . describes the influence of chorioamnionitis exposure on preterm monocyte transcription using whole transcriptome shotgun sequencing (RNA‐seq), which provides valuable information on the impact of this inflammatory exposure on neonatal innate immune function in a cell‐specific manner …”
mentioning
confidence: 99%
“…The recent paper by de Jong et al describes the influence of chorioamnionitis exposure on preterm monocyte transcription using whole transcriptome shotgun sequencing (RNA-seq), which provides valuable information on the impact of this inflammatory exposure on neonatal innate immune function in a cellspecific manner. 3 Exposure to chorioamnionitis increases the risk of developing earlyonset sepsis (within the first 72 h of birth) with conflicting data about whether it is protective against or increases susceptibility to late-onset sepsis (after 72 h of life), 1,4,5 suggesting that exposure to chorioamnionitis impacts subsequent neonatal immune function and modulates the already high infection risk in the neonatal period. Previous studies have utilized microarrays on umbilical cord blood of preterm infants exposed to chorioamnionitis and/or FIRS to evaluate the impact of this inflammatory exposure on the neonatal immune transcriptosome.…”
mentioning
confidence: 99%
See 1 more Smart Citation